Using Authentic Reading Materials from Internet to enhance the Eighth Grade Students` Reading Comprehension - Rahadhiyanti, Dyah Arum; Tasnim, Zakiyah; Sundari, Siti (English Education Study Program, 2016)
This article describes the improvement of students` readingcomprehension achievement by using authentic reading materials from internet. Theresearch design is classroom action research and the research area was at SMPN 9Jember chosen by using purposive method. The data collection methods were a test,observation, interview, and documentation. The research subjects were the studentsof VIII-C at the school chosen purposively. The results of observation showed thatthe students` participation was improved from 77% in Cycle 1 to 82% in Cycle 2.The students` reading comprehension achievement was also improved from 77% inCycle 1 and 89% in Cycle 2. It can be concluded that the use of authentic readingmaterials from internet can improve the eighth grade students` active participationand their reading comprehension achievement. Therefore the English teacher shoulduse authentic reading materials from internet to teach reading comprehension.